2015
DOI: 10.1016/j.gecco.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reserve protection level on the vulnerable fish species Sciaena umbra and implications for fishing management and policy

Abstract: a b s t r a c tThe brown meagre Sciaena umbra, an iconic demersal fish species in Mediterranean coastal habitats, is particularly vulnerable to fishing pressure and presents a worrying population decline. Fish numbers and sizes were surveyed by visual census at Scandola (Corsica) in and outside reserve zones subject to increasing levels of protection, including unprotected zones (UP) where all fishing activities are permitted, buffer zones (BZ) subject to partial protection and a totally protected no-take inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…Leleu et al [142]), while others, such as trawling, capture non-targeted species and have a stong mechanical impact upon benthic ecosystems [143][144][145][146]. Due to overfishing, most benthic ecosystems are strongly depleted in teleosts (fish), especially in invertivores (consumers of invertebrates) and top predator fish, with a dramatic decrease in mean size and in number of individuals [64,[147][148][149]. Only a very few Marine Protected Areas (MPAs), such as the Port-Cros National Park (Provence, France), the Stait of Bunifaziu Natural Reserve, the Scandula Natural Reserve (Corsica) and the Cabrera National Park (Balearic Islands), are free of this impact [40, 149,150].…”
Section: The Impact Of Overfishingmentioning
confidence: 99%
See 1 more Smart Citation
“…Leleu et al [142]), while others, such as trawling, capture non-targeted species and have a stong mechanical impact upon benthic ecosystems [143][144][145][146]. Due to overfishing, most benthic ecosystems are strongly depleted in teleosts (fish), especially in invertivores (consumers of invertebrates) and top predator fish, with a dramatic decrease in mean size and in number of individuals [64,[147][148][149]. Only a very few Marine Protected Areas (MPAs), such as the Port-Cros National Park (Provence, France), the Stait of Bunifaziu Natural Reserve, the Scandula Natural Reserve (Corsica) and the Cabrera National Park (Balearic Islands), are free of this impact [40, 149,150].…”
Section: The Impact Of Overfishingmentioning
confidence: 99%
“…Due to overfishing, most benthic ecosystems are strongly depleted in teleosts (fish), especially in invertivores (consumers of invertebrates) and top predator fish, with a dramatic decrease in mean size and in number of individuals [64,[147][148][149]. Only a very few Marine Protected Areas (MPAs), such as the Port-Cros National Park (Provence, France), the Stait of Bunifaziu Natural Reserve, the Scandula Natural Reserve (Corsica) and the Cabrera National Park (Balearic Islands), are free of this impact [40, 149,150]. As a result, there is often an increase in the pressure of herbivorous species, such as the sea urchin Paracentrotus lividus and the teleost Sarpa salpa, which are released from predation by top predators [96,151] (but see [152]).…”
Section: The Impact Of Overfishingmentioning
confidence: 99%
“…On the northwestern coasts of the Mediterranean Sea, the effects of different reserve protection levels resulted in an increased abundance and biomass of the species, suggesting the negative impact of fishing activities in the area and especially of spearfishing catches (Harmelin-Vivien et al 2015). As a vulnerable species, the brown meagre is therefore a good indicator of the efficiency of the fishing limitation measures (Harmelin and Ruitton 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As a vulnerable species, the brown meagre is therefore a good indicator of the efficiency of the fishing limitation measures (Harmelin and Ruitton 2007). On the French Mediterranean coasts, a temporary level of partial protection and a ban on all types of recreational fishing has been adopted since 2014 for the recovery of S. umbra populations (Harmelin-Vivien et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the creation of an MPA may initially result in the displacement of fishing effort to the surrounding areas (Halpern et al, 2004) and the direct benefits to fishers are observed only after a sufficient amount of time . In the Mediterranean MPAs, these benefits have been documented in a few studies and explained through three main phenomena: 1) an increase in abundance, biomass, and average size of fish (Ojeda-Martinez et al, 2007;García-Charton et al, 2008;Guidetti et al, 2014;Harmelin-Vivien et al, 2015;Giakoumi et al, 2017), 2) an enhancement of fisheries yields within the MPA (Goñi et al, 2010;Guidetti & Claudet, 2010), and finally 3) an increase in fishing catch, but also effort near the boundaries of the no-take MPAs due to the fish "spillover" effect (Stelzenmüller et al, 2007). The latter is defined as the net emigration of juveniles, subadults, and adults beyond the boundaries of the MPA resulting in fishery benefits in neighboring areas (Harrison et al, 2012;Colléter et al, 2014;Di Lorenzo et al, 2016).…”
Section: Artisanal Small-scale Fisheries and The Mediterranean Mpasmentioning
confidence: 99%